Practice makes Perfect: Shaping Influences on Informal Reading Among Adult Developing Readers - Alisa Belzer (Adult Education Research Conference, 2006)
This study of 3 adult literacy learners’ outside class text interactions, indicate that quantity and quality of reading practice may be influenced by the ways prior experiences have helped shape their beliefs and understandings about reading development, access to text, and the nature of family relationships related to learning and literacy.
Keywords: Adult literacy; reading development